In-process assessment for technological enhanced learning - Oh, Emerson Yu Yang (Nanyang Technological University, 2020)
Assessment is an essential component in the Singapore education system. In recent years, there has been a shift in the stance of assessment by the Ministry of Education Singapore, reducing the number of school-based pen-and-paper assessments all various levels. The emergence of alternative assessment methods has paved the way for many different replacements for these traditional assessments. One of these is the In-Process or Stealth Assessment, using evidence-centred design to test the presence of competencies in students through digital games. With the rise of the use of Technology Enhanced Learning platforms, In-Process Assessment can be a complimentary part of these platforms. The objective of this study is to study the use of In-Process Assessment in digital games. In this report, a study on implementing a competency model into an existing educational game will be explained, linking back to lessons learnt on the benefits of In-Process Assessment. Recommendation for future development of the framework to better fit MOE’s philosophy will be discussed. In addition, how blockchain technology has disrupted Fintech and its potential in the education sector will be evaluated.